KAJIAN USAHA PENGOLAHAN KARET (Hevea brasiliensisL) SIT ASAP RSS (Rubber Smoke Sheet) DI DESA SIMPANG TIGA KECAMATAN MATARAMAN KABUPATEN BANJAR PROVINSI KALIMANTAN SELATAN - Rohansyah Rohansyah; Subhan Fitriadi; Eddy Triatmoko; Ahmad Ramadhani (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2019)
The purpose of this research is to know the revenue,the total cost,income and break even point  of make Rubber  Smoke Sheet farming . This research was conducted in  Oktober 2018 at village Simpang Tiga, Mataraman, Banjar regency province South Kalimantan . The Purposive sampling metode used was by observing 23 farmers in Simpang tiga mataraman who.make rubber smoke sheet. The Average result of the revenue is Rp. 5.328.260,87/ farmer, the average total cost is Rp. 2.361.588,27/farmer, and total profit is Rp 2.966.672,60/farmer.. BEP  Rp. 1.288.984,64dan BEP product Rubber  Smoke Sheet 51,56kg/farming. Based on the break even point,we can know the limit result which can give benefit or disvantage. From  this result of development of farming make Rubber  Smoke Sheet we believe that it has good prospect and revenue, of the break even point ,tecnicall and economically..